Synthesis of Cannabinol by a Modified Ullmann–Ziegler Cross-Coupling - Nüllen, Max P.; Göttlich, Richard (Synlett, 2013)
Cannabinol, a pharmaceutically interesting component of cannabis, was prepared by a modified Ullmann–Ziegler cross-coupling. Using easily obtainable starting materials, this convergent approach allows facile access to a variety of cannabinol derivatives.
Keywords: natural products; cross-coupling; palladium; copper; cannabinoids